STRUCTURAL PROCESS AS A GUARANTEE FOR IMPLEMENTING SOCIAL CHANGES - Gomes Júnior, Luiz Manoel; Cardoso, Kelly; Nunes Borges, Sabrina (Revista Inclusiones, 2021)
The study aims to outline the main points of the structural process and analyze its effectiveness in complying with judicial decisions. The broad participation of society - a really adequate representation, based on an argumentative and dialogical activity, in total consonance with the due constitutional process, is an important measure for the realization of fundamental rights and democratic legitimation of the judicial activity, evidencing, therefore, the need of the process to be rethought. To this end, the research will analyze the relevant aspects of the Brazilian procedural system in the face of multipolar disputes and whether this system is sufficient to welcome the structural process, especially regarding the analysis of dialogicity as a factor for legitimizing a fair and democratic process. The Structural Process will also be investigated through a brief historical incursion.